Bis(ethylenediamine-κ(2) N,N′)(nitrato-κ(2) O,O′)cobalt(III) hydroxide nitrate - Zhang, Ji-Bo (International Union of Crystallography, 2009)
The Co ion in the title salt, [Co(NO(3))(H(2)NCH(2)CH(2)NH(2))(2)](OH)(NO(3)), has oxidation state + III and is coordinated by four N atoms from two ethylenediamine molecules and two O atoms from a nitrate anion in a distorted octahedral geometry. The charge of the complex cation is balanced by a hydroxide anion and a nitrate anion. The cations and anions are connected by N—H⋯O and O—H⋯O hydrogen bonds, resulting in a three-dimensional supramolecular framework. There are two independent ion pairs with similar configurations in the unit cell. Both uncoordinated nitrate counter-anions are disordered.